Comparative study of 18F-DCFPyL PET/CT and 99mTc-MDP SPECT/CT bone imaging for the detection of bone metastases in prostate cancer - Hu, Xiongjian; Cao, Yiming; Ji, Bin; Zhao, Min; Wen, Qiang; Chen, Bin (Frontiers in Medicine, 2023)
Purpose: This study aimed to compare the diagnostic efficiency of 18F-DCFPyL PET/CT imaging and 99mTc-MDP SPECT/CT bone imaging for the detection of bone metastases in prostate cancer. Methods: A retrospective analysis was conducted on 31 patients with confirmed prostate cancer between September 2020 and September 2022. All patients underwent 18F-DCFPyL PET/CT and 99mTc-MDP SPECT/CT bone imaging. The gold standard was the pathology or Best Valuable Comparator (BVC). Diagnostic performance indicators were analyzed at both the patient and lesion levels. Results: Of the 31 prostate cancer patients, 18 were diagnosed with bone metastases, with a total of 84 bone metastatic lesions. At the patient level, 18F-DCFPyL PET/CT imaging showed superior diagnostic performance compared to 99mTc-MDP SPECT/CT bone imaging in all indicators: sensitivity (100% vs. 77.8%, P <0.01), specificity (92.3% vs. 69.2%, P <0.05), accuracy (96.8% vs. 74.2%, P <0.01). The AUC values for 18F-DCFPyL PET/CT imaging and 99mTc-MDP SPECT/CT bone imaging were 0.962 and 0.735 (Z = 2.168, P <0.05). At the lesion level, 18F-DCFPyL PET/CT imaging showed superior diagnostic performance compared to 99mTc-MDP SPECT/CT bone imaging in all indicators: sensitivity (97.6% vs. 72.6%, P <0.01), specificity (95.7% vs. 73.9%, P <0.01), accuracy (97.2% vs. 72.9%, P <0.01). The AUC values for 18F-DCFPyL PET/CT imaging and 99mTc-MDP SPECT/CT bone imaging were 0.966 and 0.733 (Z = 3.541, P <0.001). Conclusions: Compared with 99mTc-MDP SPECT/CT bone imaging, 18F-DCFPyL PET/CT imaging demonstrated higher diagnostic efficiency for bone metastases in prostate cancer, and it can more accurately determine the presence of bone metastases.